Molecular perturbation strategies to examine spatiotemporal features of Rho GEF and Rho GTPase activity in living cells - Goedhart, Joachim (Small GTPases, 2017)
Much of our current knowledge of Rho GTPase networks and the regulation by Rho guanine exchange factors (Rho GEFs) and Rho GTPase activating proteins (Rho GAPs) is based on population-based techniques. Over the last decades, technologies that enable single cell analysis with high spatial and temporal resolution have revealed that Rho GTPase activity in cells is regulated on second timescales and at submicrometer length scales. Therefore, perturbation methods with matching spatial and temporal resolution are crucial to further our understanding of Rho GTPase signaling. Here, we give a brief overview of the components of Rho GTPase signaling networks and review a range of existing perturbation strategies that target a specific component of the Rho GTPase signaling module. The advantages and limitations of each perturbation method are discussed. Several recommendations are formulated to guide future studies aimed at addressing spatiotemporal aspects of Rho GEF and Rho GTPase signaling.